Marketing company profile: Consumer-led company features - Kovačević Ivana (Marketing (Beograd. 1991), 2005)
Starting point in defining modern company profile is its absolute orientation to customers. So called Customer-led companies are those which all their activities put toward customers instead of product which is offered. These companies try to make all their sectors to be oriented toward customers.